Developing thesaurus of the author’s literary discourse (based on P. Bazhov’s tales) - Stepanova, Liubov Iurevna; Shchukina, Daria Alekseevna (Linguistics and Culture Review, 2021)
The concept of a thesaurus is examined in the article; the importance of creating individual author’s thesauri for a better understanding of the linguistic personality of the writer and his worldview reflected in the units of the language system is determined. This provides the opportunity to conduct the diachronic study of the language and make comparative analyzes of various writers’ idiolects, etc. The individual author’s picture of the world in Bazhov’s tales using the method of comparing formal and functional thesauri proposed by L. Gasparov is examined in the article. This approach made it possible to determine the features of the language system of Bazhov’s tales with the functioning of such lexical units in it that contribute to the understanding of the niche occupied by the lexical-semantic field “precious metals and stones” and other interacting spheres in this picture of the world including natural-geographical and everyday spheres, professional and mythopoetic spheres.